Impact of a fast‐track surgery programme for pancreaticoduodenectomy. Issue 9 (4th June 2015) - Williamsson, C.; Karlsson, N.; Sturesson, C.; Lindell, G.; Andersson, R.; Tingstedt, B.
<x xml:space="preserve">Abstract</x> Background Fast‐track (FT) programmes are multimodal, evidence‐based approaches to optimize patient outcome after surgery. The aim of this study was to evaluate the safety, clinical outcome and patients' experience of a FT programme after pancreaticoduodenectomy (PD) in a high‐volume institution in Sweden. Methods Consecutive patients undergoing PD were studied before and after implementation of the FT programme. FT changes included earlier mobilization, standardized removal of the nasogastric tube and drain, and earlier start of oral intake. Patient experience was evaluated with European Organization for Research and Treatment of Cancer QLQ‐C30 and QLQ‐PAN26 questionnaires 2 weeks before and 4 weeks after surgery. Results Between 2011 and 2014, 100 consecutive patients undergoing PD were studied, of whom 50 received standard care (controls), followed by 50 patients treated after implementation of the FT programme. The nasogastric tube was removed significantly earlier in the FT group, and these patients were able fully to tolerate fluids and solid food sooner after PD. Delayed gastric emptying was significantly reduced in the FT group (26 versus 48 per cent; P = 0·030). Overall morbidity remained unchanged and there were no deaths in either group. Postoperative length of hospital stay was reduced from 14 to 10 days and hospital costs were decreased significantly. Health‐related quality‐of‐life questionnaires showed similar patterns of change, with no significant difference between groups before or after surgery. Conclusion The FT programme after PD was safe. Delayed gastric emptying, hospital stay and hospital costs were all reduced significantly. Although patients were discharged 4 days earlier in the FT group, this did not influence health‐related quality of life compared with standard care.